Associations of exposure to acrylamide and glycidamide with psoriasis among adults: Findings from a population-based study - Rui Ma; Nan Yang; Hao Mei; Yu Zhuang; Yu Wang; Yuanyuan Wang; Xin Wang; Yuling Shi (Ecotoxicology and Environmental Safety)
Acrylamide (AA), a hazardous chemical prevalent in the environment and human diet, and its metabolite glycidamide (GA) are suspected contributors to psoriasis. However, the relationship between AA, GA exposure and psoriasis incidence remains unclear. Using data from the National Health and Nutrition Examination Survey (NHANES) cycles 2003–2004, 2005–2006, and 2013–2014, we conducted a cross-sectional study involving 6999 participants. While no overall association was observed between AA-hemoglobin adduct (HbAA), HbGA levels, and psoriasis risk, subgroup analyses revealed positive relationships among individuals aged 20–40 years and those with serum cotinine levels between 0.011 and 10 ng/mL. We also assessed the relationship between HbAA, HbGA exposure and various laboratory biomarkers. HbAA exposure was positively associated with high-density lipoprotein (HDL) and white blood cell counts, but negatively associated with folate. HbGA exposure was negatively associated with HDL and vitamin B12. Interaction analyses indicated that higher levels of serum HDL, folate, vitamin B12, and peripheral white blood cell and monocyte counts attenuated the detrimental effects of HbGA exposure on psoriasis risk. Sensitivity analysis based on dietary AA intake from NHANES 24-hour dietary recall data (2003–2004, 2005–2006 cycles, N = 4932) yielded results consistent with those observed for HbAA and HbGA exposure. These findings suggest that AA and GA exposure may contribute to psoriasis incidence, particularly among younger adults and smokers, and that improving nutritional intake and lifestyle factors could help mitigate this risk. Further research is needed to confirm these associations in diverse populations and elucidate the underlying mechanisms of AA/GA-related psoriasis pathogenesis.